Subscription Page (The Review of Asset Pricing Studies, 2016)
Journal Article Subscription Page Get access The Review of Asset Pricing Studies, Volume 6, Issue 2, December 2016, Page i3, https://doi.org/10.1093/rapstu/rav017 Published: 15 November 2016